Credit Union and Bank Subprime Lending in the Great Recession - Li, Kangli; van Rijn, Jordan (The Review of Corporate Finance Studies, 2024)
Abstract Firm structure affects incentives and performance. We document significant differences in subprime lending between banks and credit unions prior to and during the Great Recession. In 2006, 23.6% of mortgages from commercial banks were subprime versus only 3.6% of mortgages from credit unions. Moreover, banks were more likely to fail, and had higher delinquency and net charge-off ratios immediately following the financial crisis. Our empirical models control for important differences between credit unions and banks including firm-level characteristics, borrower-level characteristics, and state-level economic conditions. We argue that the remaining difference captures the effects of credit unions’ nonprofit and cooperative structure, which encourages them to internalize the utility of their customer-owners. Our findings explain why credit unions often appear more risk averse relative to commercial banks, a result with important research and policy implications. (JEL G12, G31)